A comparison between endoscopic ultrasound–guided and percutaneous biliary drainage after failed endoscopic retrograde cholangiopancreatography for malignant biliary obstruction: A retrospective cohort study. Issue 1 (8th July 2022) - Chow, Hin San; Chan, Justin Chung Yan; Cheung, Wai Hung; Lai, Amanda Yun Ling; Yu, Ellen Lok Man; Lai, Tak Wing
Abstract: Aim: Endoscopic ultrasonography–guided biliary drainage (EUS‐BD) is increasingly used as an alternative therapeutic modality to percutaneous transhepatic biliary drainage (PTBD) for malignant biliary obstruction in patients who fail endoscopic retrograde cholangiopancreatography (ERCP). We conducted a retrospective study comparing the success rate and safety of the two drainage methods. Patients and Methods: There were 121 consecutive patients undergoing EUS‐BD or PTBD who had malignant biliary obstruction that failed to be treated by ERCP at Princess Margaret Hospital between August 2015 and May 2021. Thirty‐five patients with biliary obstruction at or proximal to hilar level were excluded from this study. A retrospective cohort study was performed for 26 patients who underwent EUS‐BD (choledochoduodenostomy or hepaticogastrostomy) and 60 patients who underwent PTBD. Their clinical data and endoscopic data, demographic data, diagnosis, laboratory data, complications, number of re‐interventions, in‐hospital death and length of hospitalisation were extracted and compared. Results: The clinical success rates for EUS‐BD and PTBD were 25 out of 26 (96.2%) and 43 out of 60 (71.7%), respectively ( P  = .01). The technical success rates were 25 out of 26 (96.2%) and 57 out of 60 (95.0%), respectively ( P  > .99). Among those technically successful cases, complications were significantly fewer in the EUS‐BD group (4%) than in the PTBD group (33.3%). There were significantly fewer re‐interventions, shorter length of hospitalisation and fewer in‐hospital death in the EUS‐BD group. No significant difference in stent/PTBD patency was noted between the two groups. Conclusion: EUS‐BD is a safe and effective method of BD in patients with malignant biliary obstruction who failed ERCP. EUS‐BD has a higher rate of clinical success, is associated with fewer complications and has a shorter length of in‐hospital stay compared with PTBD. The overall technical success and stent patency are comparable to PTBD.